RELATIONSHIP MODEL OF WORKLOAD, WORK MOTIVATION, AND WORK DISCIPLINE ON THE PERFORMANCE OF SHARIA BANKING EMPLOYEES IN JAKARTA - Nur Affini, Dinar; Hikmah Perkasa, Didin (Dinasti Publisher, 2021)
This study was conducted to analyze the relationship model between workload, work motivation, and work discipline on the performance of banking employees in Jakarta. The research design is descriptive quantitative causal, where the object of this research is banking employees in Jakarta as many as 100 people. Data analysis using SPSS test tool will be tested for validity, reliability test, normality test, multicollinearity, heteroscedasticity, multiple linear regression, and hypothesis testing. In this study there are three hypotheses where the test results show that partially the workload, work motivation, and work discipline variables affect the performance of Islamic banking employees in Jakarta.